2015
DOI: 10.1210/jc.2015-2675
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Cardiomyopathy Using Cardiac Magnetic Resonance Imaging in an Acromegaly Contemporary Cohort

Abstract: We demonstrated by CMRi, the gold-standard method, that patients with active acromegaly might have a lower prevalence of cardiac abnormalities than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 35 publications
2
32
1
2
Order By: Relevance
“…The EF was normal in all patients, and only 5% were diagnosed with left ventricular hypertrophy. The examination was repeated after 12 months of treatment, but there were no statistically significant differences in the obtained results independently of the dynamics of the GH and IGF-1 values, indicating biochemical disease control [ 24 ]. Fazeli et al expressed similar doubts regarding the influence of GH and IGF-1 on the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…The EF was normal in all patients, and only 5% were diagnosed with left ventricular hypertrophy. The examination was repeated after 12 months of treatment, but there were no statistically significant differences in the obtained results independently of the dynamics of the GH and IGF-1 values, indicating biochemical disease control [ 24 ]. Fazeli et al expressed similar doubts regarding the influence of GH and IGF-1 on the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology underlying cardiac involvement in acromegaly is not clearly understood, elevated GH serum levels and consequent plasma volume expansion and direct anti‐natriuretic effect, increased peripheral vascular resistance may be the cause. LVH and myocardial fibrosis are considered common findings in acromegalic cardiomyopathy in echocardiography studies . However, there is limited information on LA function in acromegaly …”
Section: Discussionmentioning
confidence: 99%
“…Bogazzi et al (22) demonstrated that acromegaly patients with controlled disease after using somatostatin analogs had a greater reduction in the LV mass index than those without controlled disease. dos Santos Silva et al (23) found no clinically relevant cardiac improvements after medical therapy with octreotide. Andreassen et al (21), however, reported a decrease in cardiac function 3 months after treatment.…”
Section: Introductionmentioning
confidence: 96%
“…Evaluations of the heart with the gold standard cardiovascular magnetic resonance (CMR) offer objective and reproducible results, and CMR can precisely assess cardiac structure and function and even evaluate parameters that are difficult to precisely assess by echocardiography, such as myocardial fibrosis and ventricular volumes (16)(17)(18)(19). Several studies have used CMR to evaluate cardiac involvement in acromegaly patients (20)(21)(22)(23)(24)(25), and the results of these studies showed that the incidence rates of myocardial fibrosis, left ventricular (LV) systolic dysfunction (LVSD), and LV hypertrophy in acromegaly patients were 0% to 14.8%, 0% to 12.5%, and 5% to 72%, respectively. Some of these studies focused on the posttreatment reversibility of cardiac involvement, but the results are controversial.…”
Section: Introductionmentioning
confidence: 99%